Abdul Hamid Hakim: An Important Figure in the Transmission of the Ushul Fiqh in Indonesia - Yahya Yahya; Romli SA; Muhajirin Muhajirin; Arwansyah bin Kirin (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
This study explores the pivotal role of Abdul Hamid Hakim in the transmission and development of ushul fiqh in Indonesia during the first half of the 20th century. As a prominent scholar, Abdul Hamid Hakim made significant contributions through his works, such as Mabadi Awwaliyyah, As Sullam, and Al Bayan, which introduced a systematic and structured methodology in ushul fiqh and enriched the discourse with innovative legal principles. The research aims to analyze Abdul Hamid Hakim’s intellectual contributions and their impact within the socio-cultural context of Indonesia. Using a qualitative approach with historical-biographical methods and content analysis, the study examines his works and their role in shaping Islamic legal education and scholarship. The findings reveal that Abdul Hamid Hakim’s works remain foundational references in academic and religious institutions, bridging classical Islamic scholarship with contemporary needs. This research highlights his enduring influence in developing Islamic law in Indonesia. Penelitian ini mengeksplorasi peran penting Abdul Hamid Hakim dalam transmisi dan pengembangan ushul fiqh di Indonesia selama paruh pertama abad ke-20. Sebagai seorang ulama terkemuka, Abdul Hamid Hakim memberikan kontribusi signifikan melalui karya-karyanya, seperti Mabadi Awwaliyyah, As Sullam, dan Al Bayan, yang memperkenalkan metodologi sistematis dan terstruktur dalam ushul fiqh dan memperkaya wacana dengan prinsip-prinsip hukum yang inovatif. Penelitian ini bertujuan untuk menganalisis kontribusi intelektual Abdul Hamid Hakim dan dampaknya dalam konteks sosial budaya Indonesia. Dengan menggunakan pendekatan kualitatif dengan metode historis-biografis dan analisis konten, penelitian ini mengkaji karya-karyanya dan perannya dalam membentuk pendidikan dan beasiswa hukum Islam. Temuan penelitian mengungkapkan bahwa karya-karya Abdul Hamid Hakim tetap menjadi referensi mendasar dalam lembaga akademik dan keagamaan, menjembatani beasiswa Islam klasik dengan kebutuhan kontemporer. Penelitian ini menyoroti pengaruhnya yang abadi dalam pengembangan hukum Islam di Indonesia.